The effect of lectins on the attachment and invasion of Enteromyxum scophthalmi (Myxozoa) in turbot (Psetta maxima L.) intestinal epithelium in vitro - Redondo, Mª José; Álvarez-Pellitero, Mª del Pilar (Experimental Parasitology, 2010)
21 p., figuras y bibliografía The involvement of the lectin/carbohydrate interaction in the invasion of the turbot intestinal epithelium by Enteromyxum scophthalmi was studied in vitro using explants of turbot intestine and pre-treatment of parasite stages with the plant lectins of Canavalia ensiformis (Con A) and Glycine max (SBA). Both lectins inhibited the attachment and invasion of E. scophthalmi stages to the intestinal epithelium, though the inhibitory effect was higher for SBA than for Con A. Such results point to the involvement of N-acetyl-galactosamine (GalNAc) and galactose (Gal) residues and also of mannose/glucose residues in the E. scophthalmi-intestinal epithelium interaction. The inhibitory effect of both lectins on the parasite adhesion and penetration points to the interest of further studies to confirm the presence of putative lectins recognising GalNAc-Gal and mannose/glucose residues in turbot intestine. The obtained results demonstrated also the adequacy of turbot intestinal explants as an in vitro model to study the interaction with E. scophthalmi. This work was supported by the Spanish Ministry of Science and Education through the research projects AGL2006-13158-C01 and AGL2009-13282-C02-01. María J. Redondo is recipient of a CSIC I3P contract funded by the European Social Fund. Peer reviewed